Nerve Surgery to Treat Intractable Genitofemoral Neuropathic Pain following Laparoscopic Live Kidney Donation - K. Ramdhani; M. J. A. Malessy; M. J. G. Simon; V. A. L. Huurman (Case Reports in Transplantation)
To date live laparoscopic donor nephrectomies (LLDN) are frequently performed. The most common complications entail bleeding, wound infection, and incisional hernia. Here we discuss a 50-year-old patient with a severe less known complication, namely, postoperative persistent neuropathic pain in the scrotum and left upper leg. Satisfactory pain control could not be obtained in 3 years of postoperative pain treatment which consisted of neuroleptic drugs, blocks of the L1/L2 dorsal roots with local anaesthetics, and pulsed radiofrequency lesioning. Exploratory laparoscopy was performed to assess the aspect of the genitofemoral nerve (GFN). A hemoclip used for the closure of the ureter at the time of nephrectomy was found in close relation to the GFN. The clip was removed and the GFN was subsequently cut proximal to the side of this clip. Soon after surgery the patient was completely pain-free and could return to his normal activities. Surgery should be considered in case of GFN neuropathic pain following LLDN.